Calcipotriol Plus Betamethasone Dipropionate Aerosol Foam in Patients with Moderate-to-Severe Psoriasis: Sub-Group Analysis of the PSO-ABLE Study - Paul, Carle (Am J Clin Dermatol, 2017)
BACKGROUND: Fixed-combination calcipotriol 50 μg/g plus betamethasone 0.5 mg/g (Cal/BD) aerosol foam is a new topical treatment for psoriasis. Although moderate-to-severe psoriasis is typically treated with systemic/biologic therapies, a topical treatment that is efficacious in these patients may be a significant cost-saving alternative to systemic therapy. OBJECTIVE: The objective of this study was to assess the response to Cal/BD foam and gel in patients with moderate-to-severe psoriasis enrolled in the phase III, 12-week PSO-ABLE study. METHODS: Patients eligible for this analysis had moderate-to-severe psoriasis, defined by the ‘Rule of Tens’: body surface area ≥10% or Psoriasis Area and Severity Index (PASI) [excluding head; modified PASI (mPASI)] >10 or Dermatology Life-Quality Index >10. Endpoints included: proportion of patients achieving mPASI75 or mPASI90; change in body surface area; proportion of patients clear/almost clear with a ≥2 grade improvement (i.e., treatment success); change in Dermatology Life-Quality Index. RESULTS: Seventy-seven Cal/BD foam patients and 82 gel patients had moderate-to-severe psoriasis. A greater proportion achieved mPASI75 and mPASI90 with Cal/BD foam than gel at weeks 4, 8, and 12 (57.1 vs. 35.4%; p = 0.006 and 15.6 vs. 12.2% at week 12, respectively); overall reduction in mPASI from baseline to week 12 was 64% with the foam vs. 51% with the gel. Overall reduction in body surface area at week 12 was 50% with the foam and 39% with the gel. Treatment success rates were higher with the Cal/BD foam than the gel at weeks 1, 2, 4, 8 (p = 0.0089), and 12, and a greater proportion of foam patients achieved a Dermatology Life-Quality Index score of 0/1 at weeks 4 (p = 0.004), 8, and 12 (p = 0.001). CONCLUSION: Cal/BD foam can be considered as a treatment option in some patients with moderate-to-severe psoriasis who are potential candidates for systemic therapy. CLINICALTRIALS.GOV IDENTIFIER: NCT02132936.